SUSTAINABLE BLUE MARITIME POTENTIALS IN SEBONG LAGOI: ECOTOURISM, CARBON CAPTURE, AND COMMUNITY EMPOWERMENT - Muhammad Isa Alamsyahbana; Indra Bastian Tahir; Rachmad Chartady; Juliani Sari Siregar; Rizky Ramadhana Putra; Airina Cintha Sepriana Sulfat (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
The purpose of this paper is to explore the opportunities of the blue maritime economy in Bintan Island, particularly in Sebong Lagoi, by examining the intersections of ecotourism, conservation, carbon capture, and community-based economic empowerment. This study employs a qualitative descriptive approach to examine the potential of mangrove ecosystems as both ecological and economic assets. The methodology includes field observation, document review of policy and regulatory frameworks, and analysis of secondary literature, using thematic categorization as the main analytical tool. The findings indicate that mangrove ecosystems in Bintan hold significant potential for eco-edu-tourism, fisheries sustainability, and community-based enterprises such as village-owned businesses (BUMDes). The analysis also highlights the role of mangroves as carbon sinks that can be linked to carbon markets, including IDX Carbon, offering pathways for sustainable financing. This study is limited to qualitative insights and exploratory observations in Sebong Lagoi, Bintan. Future research may consider comparative or quantitative approaches, including economic valuation of carbon sequestration and broader stakeholder analysis, to enhance generalizability. The results provide insights for practitioners and policymakers in designing integrated blue economy policies that align ecotourism, conservation, and carbon market opportunities with local economic empowerment. The paper contributes to understanding how blue maritime initiatives can foster inclusive growth, enhance community resilience, and promote global environmental stewardship through carbon capture and conservation awareness. This study offers a novel perspective by examining the convergence of blue economy practices, mangrove-based carbon capture, and community-driven development in Bintan Island, contributing to the discourse on sustainable maritime economies in Southeast Asia.